Lung tissue bioenergetics and caspase activity in rodents - Alsuwaidi Ahmed R; Alsamri Mohammed T; Alfazari Ali S; Almarzooqi Saeeda; Albawardi Alia; Othman Aws R; Pramathan Thachillath; Hartwig Stacey M; Varga Steven M; Souid Abdul-Kader (BMC Research Notes, 2013)
Abstract Background This study aimed to establish a suitable in vitro system for investigating effects of respiratory pathogens and toxins on lung tissue bioenergetics (cellular respiration and ATP content) and caspase activity. Wistar rats and C57Bl/6 mice were anesthetized by sevoflurane inhalation. Lung fragments were then collected and incubated at 37°C in a continuously gassed (with 95% O2:5% CO2) Minimal Essential Medium (MEM) or Krebs-Henseleit buffer. Phosphorescence O2 analyzer that measured dissolved O2 concentration as a function of time was used to monitor the rate of cellular mitochondrial O2 consumption. Cellular ATP content was measured using the luciferin/luciferase system. The caspase-3 substrate N-acetyl-asp-glu-val-asp-7-amino-4-methylcoumarin (Ac-DEVD-AMC) was used to monitor intracellular caspase activity; cleaved AMC moieties (reflecting caspase activity) were separated on HPLC and detected by fluorescence. Lung histology and immunostaining with anti-cleaved caspase-3 antibody were also performed. Results For Wistar rats, the values of kc and ATP for 0 < t ≤ 7 h (mean ± SD) were 0.15 ± 0.02 μM O2 min-1 mg-1 (n = 18, coefficient of variation, Cv = 13%) and 131 ± 69 pmol mg-1 (n = 16, Cv = 53%), respectively. The AMC peak areas remained relatively small despite a ~5-fold rise over 6 h. Good tissue preservation was evident despite time-dependent increases in apoptotic cells. Lung tissue bioenergetics, caspase activity and structure were deleterious in unoxygenated or intermittently oxygenated solutions. Incubating lung tissue in O2 depleted MEM for 30 min or anesthesia by urethane had no effect on lung bioenergetics, but produced higher caspase activity. Conclusions Lung tissue bioenergetics and structure could be maintained in vitro in oxygenated buffer for several hours and, thus, used as biomarkers for investigating respiratory pathogens or toxins.